Peningkatan Peningkatan Kualitas Produksi Keripik Tette Khas Madura Menggunakan Mesin Press Semi Automatic Foodgrade Based : - - Novita Sari, Handini; Ramadani, Ali Hasbi; Alit, Ronggo (Universitas Negeri Surabaya, 2024)
Tette keripiks are a traditional food typical of the Madura region, it is proven that to this day this food is still one of the icons of typical Madurese food. However, there is still little attention from the government for the development of this specialty food industry. People's expertise in making tette keripiks has been passed down from generation to generation. Based on the results of observations and interviews by the proposing team with groups of small Tette business entrepreneurs who are program partners, it is known that the priority problems are causing the MSMEs of Tette keripiks to not develop, because the production process does not use adequate technology. Based on these problems, the solution offered to solve the problems faced by Ibu Hamiyah's Tette keripiks MSME partners is to apply research results in the form of appropriate technology produced by universities, in this case the application of the technology offered is a Semi-Automatic Tette Keripiks Press Machine Based Food grade. It is hoped that using appropriate technology will increase the quantity and quality of production from Ibu Hamiyah's Tette keripiks MSMEs. Keywords: Tette keripiks, Madurese food, appropriate technology, Press Machine